HUBUNGAN ANTARA ORIENTASI STRATEGIS DAN KEMAMPUAN INOVASI BERBASIS LAYANAN STUDI PADA UMKM KREATIF DI INDONESIA - Dwitya Aribawa (Jurnal Manajemen., 2015)
Creative industry is becoming competitive advantages to Indonesia. It has huge potency of intellectual capital around islands. Creative business aim to creating innovative business model and open absorb labor force. The objective of this study is to examine and analyze the relationships between strategic orientation (in this research consist of three dimensions; customer orientation, competitor orientation and cost orientation)and service innovation capability. Object of this study was Micro, Small and Medium Enterprises (MSMEs) that operates in one of creative subsector industry and located at in Bandung, Denpasar, Jakarta or Yogyakarta. By using quantitative analysis, this study analyzed the relationship between independent and dependent variables through testing hypotheses using ordinary least square method. Open question method also used to show the pattern of creative business development from owners point of viewt. The result of this study found customer orientation and cost orientation positively related to service innovation capability. While, competitor orientation shows not have significant relationship to service innovation capability. From this research can be conclude that creative business (MSMEs) has focus on deserve customers interest. Besides, at the same time they create efficiency in cost. Mix of both orientations in the end will creating innovation culture that fit to their business environment.